solve for y in the second equation
y = 3 + 5x
substitute into equation 1
5x - 2(3 + 5x) = -5
5x - 6 - 10x = -5
-5x = 1
x = -1/5
substitute x back into the revised 2nd equation
y = 3 + 5(-1/5)
y = 3 - 1
y = 2
2007-01-24 15:25:13
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
Take the 2nd equation and upload the 5x to the the two aspects: y - 5x = 3 y = 5x + 3 Plug this into the 1st equation: 5x - 2y = -5 5x - 2(5x + 3) = -5 5x - 10x - 6 = -5 -5x = a million x = -a million/5 Plugging this into the 2nd equation: y - 5x = 3 y - 5(-a million/5) = 3 y + a million =3 y = 2
2016-12-16 12:56:27
·
answer #2
·
answered by ? 4
·
0⤊
0⤋
solve second eqn for y
y = 3 + 5x. Sub into first eqn for y
5x - 2(3+5x)= -5
5x - 6 -10x = -5
-5x = 1
x = -1/5
so y = 3 + 5(-1/5) or 2
2007-01-24 15:25:34
·
answer #3
·
answered by leo 6
·
0⤊
0⤋
the 2nd equation is the same as y = 5x + 3
so substitute that into the first equation:
5x - 2(5x + 3) = -5
You do the rest.
Aw, c'mon you guys, don't totally do the problems for them!
2007-01-24 15:26:18
·
answer #4
·
answered by banjuja58 4
·
0⤊
0⤋
5x - 2y = -5
y - 5x = 3
y - 5x = 3
y = 5x + 3
5x - 2(5x + 3) = -5
5x - 10x - 6 = -5
-5x = 1
x = (-1/5)
y = 5(-1/5) + 3
y = -1 + 3
y = 2
ANS :
x = (-1/5)
y = 2
2007-01-24 17:24:05
·
answer #5
·
answered by Sherman81 6
·
0⤊
0⤋
I always loved the substitution method - nice little gimmee on an exam.
Two equations, two unknowns - relate one to the other and then substitute.
One equation, one unknown - solve and go after the other unknown.
2007-01-24 15:31:02
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋